2015
DOI: 10.1016/j.renene.2015.03.045
|View full text |Cite
|
Sign up to set email alerts
|

Methyl ester production from palm fatty acid distillate using sulfonated glucose-derived acid catalyst

Abstract: a b s t r a c tA highly potential heterogeneous solid acid catalyst derived from a carbohydrate precursor was successfully developed and applied for biodiesel production from palm fatty acid distillate (PFAD). The catalyst was synthesized by sulfonating the incomplete carbonized D-glucose using concentrated sulfuric acid to produce a sulfonated glucose-derived acid catalyst. The catalyst underwent a detailed characterization analysis in terms of its functional groups of active sites, morphological structure, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 104 publications
(51 citation statements)
references
References 34 publications
(63 reference statements)
2
45
0
3
Order By: Relevance
“…The activation of ICS by thermal treatment with concentrated H 2 SO 4 caused the surface area of the catalyst to increase from 10.54 m 2 g À1 to 12.40 m 2 g À1 as shown in Table 2 due to the small destruction on the carbon network producing the smaller particles. However, the average pore volume and pore size decreased slightly, suggesting that the SO 3 H groups were incorporated inside the pores of the carbon catalyst (Lokman et al, 2015). These results are significant compared to the surface areas of glucose catalyst reported by Okamura et al (2006) which was 2 m 2 g À1 , cellulose-based catalyst reported by Nakajima and Hara (2012) which was <5 m 2 g À1 , and sulfonated-lignin catalyst by Guo et al (2012) which was 4.7 m 2 g À1 .…”
Section: Characterization Of Ics-so 3 H Catalystmentioning
confidence: 75%
See 1 more Smart Citation
“…The activation of ICS by thermal treatment with concentrated H 2 SO 4 caused the surface area of the catalyst to increase from 10.54 m 2 g À1 to 12.40 m 2 g À1 as shown in Table 2 due to the small destruction on the carbon network producing the smaller particles. However, the average pore volume and pore size decreased slightly, suggesting that the SO 3 H groups were incorporated inside the pores of the carbon catalyst (Lokman et al, 2015). These results are significant compared to the surface areas of glucose catalyst reported by Okamura et al (2006) which was 2 m 2 g À1 , cellulose-based catalyst reported by Nakajima and Hara (2012) which was <5 m 2 g À1 , and sulfonated-lignin catalyst by Guo et al (2012) which was 4.7 m 2 g À1 .…”
Section: Characterization Of Ics-so 3 H Catalystmentioning
confidence: 75%
“…The presence of symmetric and asymmetric CAOASO 3 H functional groups for ICS-SO 3 H catalyst was detected by the strong absorption bands that had occurred at 1030 cm À1 and 1140 cm À1 stretching vibrations (Guo et al, 2012). Meanwhile, the weak absorption bands identical to the S‚O symmetric and asymmetric were also observed for ICS sample -this is due to the IR absorption ability of the carbon (CAC) catalyst's framework (Lokman et al, 2015).…”
Section: Characterization Of Ics-so 3 H Catalystmentioning
confidence: 94%
“…The AC-KSC on the other hand has one peak, whose corresponding temperature (526 K) signifies a weak acid site [22]. The KSC shows an insignificant ammonia desorption peak, recorded from 453 K to 483 K but which lacks the intensity and acid density needed to be fit for protonation [23]. Moreover, this peak could be as a result of the interaction between the -NH 3 with incompletely formed carbon sheets and the -SO 3 H functional group [24].…”
Section: Acid Densitymentioning
confidence: 99%
“…residues obtained after hydrolysis is comparable to those which have been successfully employed in the synthesis of biodiesel and hydrolysis of cellobiose. Carbon-based solid acid catalyst derived from sugars like glucose (Lokman et al, 2015), sucrose, and starch (Lokman et al, 2016) which had a total acid density of 4.2, 7.0, and 12.5 mmol H + /g, respectively, and were successfully used in the synthesis of fatty acid methyl ester having high biodiesel yields of 89 to 94%. Suganuma et.al (Suganuma et al, 2010) also synthesized solid acid catalyst, but using microcrystalline cellulose as the raw material, which resulted in a catalyst with a TAD of 7.3 mmol H + /g and was successfully used in the complete hydrolysis of cellobiose.…”
Section: Figurementioning
confidence: 99%